PENGARUH ANGGARAN BELANJA TERHADAP REALISASI ANGGARAN BELANJA PADA SMAN 1 BANJARAN - HASBI BASITH SUKARNO HASBI BASITH SUKARNO; RAHMAT RUSTIAWAN RAHMAT RUSTIAWAN (POLITEKNIK PIKSI GANESHA, 2019)
This study consist of two variabels, i.e. the effect of budget variabel (X) and budget realization variabel (Y). In general, this study aims to determine the influence of budget toward budget realization. This study use two methods of research is descriptive method and quantitative method and supported by literature study and data collection tool in the from of budget realization. The population in this study is the data of budget and budget realization during period 2010 to 2014, while the data samples are obtained from budget realization during the period 2010 to 2014. Based on the calculation of correlation coefficient analysis, it is obtained that the correlation result or level of the relationship between the budget toward budget realization is 0,934. The testing on the influence of the budget at SMAN 1 Banjaran can be concluded with the values of determination coefficient of 0,890 or 81%. This means that budget gives 89% influence on budget realization at SMAN 1 Banjaran the remaining 11% is influenced by other factors not examined. The suggestion given were by: 1) Maintenance of buget so that will not decrease of budget realization t; 2) Using budget effectively and efficiently; and 3) Support teaching and learning activities.